2022
DOI: 10.3390/metabo12030265
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles in Childhood and Adolescence Are Associated with Fetal Overnutrition

Abstract: Fetal overnutrition predisposes offspring to increased metabolic risk. The current study used metabolomics to assess sustained differences in serum metabolites across childhood and adolescence among youth exposed to three typologies of fetal overnutrition: maternal obesity only, gestational diabetes mellitus (GDM) only, and obesity + GDM. We included youth exposed in utero to obesity only (BMI ≥ 30; n = 66), GDM only (n = 56), obesity + GDM (n = 25), or unexposed (n = 297), with untargeted metabolomics measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Levels of branched-chain amino acids (valine and leucine) have been shown to be significantly higher in obese compared to lean children [ 33 , 34 ]. A recent study also found that exposure to any fetal overnutrition was associated with changes in children’s metabolic profiles, including the sphingomyelin-mannose, skeletal muscle, and 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid profiles [ 35 ]. Our study demonstrated that the association between branched-chain amino acids and childhood obesity is not evident during pregnancy or at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of branched-chain amino acids (valine and leucine) have been shown to be significantly higher in obese compared to lean children [ 33 , 34 ]. A recent study also found that exposure to any fetal overnutrition was associated with changes in children’s metabolic profiles, including the sphingomyelin-mannose, skeletal muscle, and 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid profiles [ 35 ]. Our study demonstrated that the association between branched-chain amino acids and childhood obesity is not evident during pregnancy or at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low quality of evidence identified in this systematic review, there is need for prospective cohort studies in diverse populations with granular data collection on prognostic risk factors as well as clinical and subclinical outcomes; high fidelity of follow-up across the lifecourse but, in particular, during sensitive windows of development during which there is greater developmental plasticity to respond to external cues 103 ; consideration of appropriate adjustment covariates depending on the specific prognostic risk factor of interest (e.g., there is discourse regarding whether maternal pre-pregnancy BMI should be included as a covariate in models where GDM severity is the prognostic risk factors of interest given that these two variables likely share overlapping in utero programming pathways 117,118 ); and appropriate causal inference 104 and analytical approaches 105 to address structural biases that afflict observational study designs.…”
Section: Future Directionsmentioning
confidence: 99%
“…A large literature on the in utero origins of childhood obesity suggests that maternal obesity and hyperglycemia may have a role in programming offspring risk of adiposity starting in early life . Observational studies have found independent associations of maternal glucose and body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) with offspring adiposity and metabolic traits, even below thresholds of gestational diabetes (GDM) . These data suggest other glycemic, as well as nonglycemic metabolic factors, such as lipids and free fatty acids (FFAs), may also play important roles in fetal programming that may operate across the continuum of maternal weight status and glucose metabolism in pregnancy …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Observational studies have found independent associations of maternal glucose and body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) with offspring adiposity and metabolic traits, even below thresholds of gestational diabetes (GDM). [4][5][6][7][8][9][10][11][12][13][14][15] These data suggest other glycemic, as well as nonglycemic metabolic factors, such as lipids and free fatty acids (FFAs), [16][17][18][19][20][21] may also play important roles in fetal programming that may operate across the continuum of maternal weight status and glucose metabolism in pregnancy. 18,19 Several studies have examined the association of individual or classes of metabolic biomarkers such as glucose, insulin, lipoproteins, and FFAs with offspring adiposity.…”
Section: Introductionmentioning
confidence: 99%